VANGUARD1 Encodes a Pectin Methylesterase That Enhances Pollen Tube Growth in the Arabidopsis Style and Transmitting Tract - Jiang, Lixi (American Society of Plant Biologists, 2005)
In flowering plants, penetration of the pollen tube through stigma, style, and transmitting tract is essential for delivery of sperm nuclei to the egg cells embedded deeply within female tissues. Despite its importance in plant reproduction, little is known about the underlying molecular mechanisms that regulate the navigation of the pollen tube through the stigma, style, and transmitting tract. Here, we report the identification and characterization of an Arabidopsis thaliana gene, VANGUARD1 (VGD1) that encodes a pectin methylesterase (PME)-homologous protein of 595 amino acids and is required for enhancing the growth of pollen tubes in the style and transmitting tract tissues. VGD1 was expressed specifically in pollen grain and the pollen tube. The VGD1 protein was distributed throughout the pollen grain and pollen tube, including the plasma membrane and cell wall. Functional interruption of VGD1 reduced PME activity in the pollen to 82% of the wild type and greatly retarded the growth of the pollen tube in the style and transmitting tract, resulting in a significant reduction of male fertility. In addition, the vgd1 pollen tubes were unstable and burst more frequently when germinated and grown on in vitro culture medium, compared with wild-type pollen tubes. Our study suggests that the VGD1 product is required for growth of the pollen tube, possibly via modifying the cell wall and enhancing the interaction of the pollen tube with the female style and transmitting tract tissues.